Analysis of The Influence of Customer Experience and Brand Image on Repurchase Decision Through Customer Satisfaction as an Intervening Variable: A Study on Apple Products at Ibox Medan - Siregar , Lamriama Valintina Chrystina; Fadli; Sembiring, Beby Karina Fawzeea (Indonesian Journal Publisher, 2026)
This study aims to analyze the influence of Customer Experience and Brand Image on Repurchase Decision with Customer Satisfaction as a mediating variable among Apple product consumers at iBox Medan. The research employs an associative quantitative approach using a survey method. The population consists of Apple users in Medan City, with a total of 150 respondents selected through a purposive sampling technique. Data were collected through questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The results reveal that both Customer Experience and Brand Image have a positive and significant direct effect on Customer Satisfaction and Repurchase Decision. Moreover, Customer Satisfaction also has a positive and significant impact on Repurchase Decision. The mediation test results indicate that Customer Satisfaction partially mediates the relationship between Customer Experience and Brand Image on Repurchase Decision. These findings suggest that a positive customer experience and a strong brand image enhance satisfaction and encourage consumers to repurchase Apple products.